Discriminatory attitudes and indigenous language promotion: Challenges and solutions - Rajesh Ramachandran; Christopher Rauh (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
In this paper, we analyse which channels influence individual preferences concerning the choice of the official language in Zambia. We develop a theoretical framework, which is tested using data on elicited beliefs about the effects of changes in Zambia's language policy on schooling outcomes, income, and social cohesion. In general, support for the use of local languages in education and government administration is low. We find that the perceived ease of learning in a local language compared to English, and economic expectations in terms of effects on income are important determinants of the preference for the use of a local language as official language. Individuals in fear of discrimination or disadvantages arising from the use of indigenous language are less likely to prefer these as official languages. However, while we do not find a systematic bias caused by the (lack of ) information about other countries' language policies, we do find that general knowledge of language policies is remarkably low. Our reading of the evidence is that individuals conflate knowledge with the medium of knowledge, and therefore prefer English as an official language despite its relative distance to their own language(s).
Keywords: 330; language policy; Zambia; discrimination; beliefs; education policy; minorities; fractionalization; local languages